Combinatorial Necklace Splitting - Pálvölgyi, Dömötör (The Electronic Journal of Combinatorics, 2009)
We give a new, combinatorial proof for the necklace splitting problem for two thieves using only Tucker’s lemma (a combinatorial version of the Borsuk-Ulam theorem). We show how this method can be applied to obtain a related recent result of Simonyi and even generalize it.